Synthesis, structural and optical properties of (ALa)(FeMn)O6 (A = Ba and Sr) double perovskites - Kumar D.; Sudarshan V.; Singh A.K. (My University, 2025)
Here, we report structural and optical properties of ALaFeMnO6 (A = Ba and Sr) double perovskite synthesized via auto-combustion followed by calcinations process. Rietveld refinement of structure using x-ray diffraction data reveals that BaLaFeMnO6 crystallizes into cubic crystal structure with space group Pm-3m while SrLaFeMnO6 crystallizes into rhombohedral crystal structure having space group R-3c. The absorption spectrum measurement using UV-Vis spectroscopy reveals that these samples are prefect insulator having energy band gap between conduction and valence band of the order of 6 eV. © 2018 Author(s).